(untitled) (African Journal of Biomedical Research, 2023)
The preventive effect of Apis dorsata honey (ADh) on the number of Leydig cells and seminiferous tubule diameter of mice (Mus musculus) exposed to monosodium glutamate (MSG) was investigated. 25 mice were divided into 5 groups. In C- group only distilled water was given. The C+ group was given 4mg/gBW of MSG while groups T1, T2 and T3 were given Apis dorsata forest honey with dosage of 53.82 mg/20g, 107.64 mg/20g and 161.46 g/20g respectively in addition to 4mg/gBW MSG. All treatments were given per oral for 52 days. Leydig cell population in the control group was 44±1.64. These values were significantly reduced in the animals exposed to MSG. Significant reversal of the effect of MSG was observed in the animals treated with Apis dorsata honey (28.56±1.47, 38.28±1.37 and 42.68±1.39 for T1, T2 and T3 respectively). Seminiferous tubular diameter was also significantly reduced by MSG (158.53±5.21 μm) when compared with the control (199.13±4.78 μm; p<0.05) while Apis dorsata honey administration attenuated the toxic effects of MSG. The results showed no significant difference (p>0.05) between the T3 and C- groups on the Leydig cell and seminiferous tubules diameter variable. It can be concluded that administration of Apis dorsata honey can maintain the number of Leydig cells and the diameter of the Seminiferous Tubules in mice exposed to MSG.